Highly sensitive rapid detection of urinary extracellular vesicles with upconverting nanoparticle based lateral flow immunoassay - Ali, Klinton (My University, 2024)
Bladder Cancer (BlCa) poses a substantial health burden globally, demanding advancements in diagnostic methodologies. Presently, existing approaches, while effective, are invasive and costly. Thus, we approach an upconverting nanoparticle (UCNP) based-lateral flow immunoassay (LFIA) to directly detect extracellular vesicles (EVs) from cancer cell lines and urine samples. Quantitative LFIAs were performed utilizing anti-tetraspanin antibody specifically, CD63 as a capture, while RAM (Rabbit Anti-Mouse Antibody) served as a control. This anti-CD63 antibody and RAM were printed onto a nitrocellulose membrane. The tracer, labeled with upconverting nanoparticles, was subsequently assessed for its detection capacity. Assay standards were established using EVs-isolated from cancer cell line. Validation of CD63-positive EVs in urine specimens was carried out using pool of urinary EVs (uEVs). Finally, uEVs from individual patients with BlCa (n=31), benign prostate hyperplasia (BPH) (n=31), and healthy (n=30) samples were captured using anti-CD63 antibody. Subsequently, the same CD63 antibody as a tracer labeled with UCNPs was used to detect these uEVs within microtitration wells. Following absorption from the mixture of sample and reporter solution onto the lateral flow strip, the strips were read with an Upcon reader device, resulting in up-converted luminescent signals after 1.2 hours. The results from this study demonstrate its high sensitivity in detecting EVs derived from cancer sources, with a detection limit of 1.9 × 105/ µL. Specifically, the CD63-CD63-UCNP assay was able to distinguish significantly between BlCa patients and individuals with benign conditions (p= 0.003), as well as healthy individuals (p= 0.0001). However, more samples are required to further validate this study. Our approach can detect EVs with high sensitivity. In future, based on our developed UCNP-LFIA, cancer associated biomarkers will be evaluated to detect bladder cancer more specifically.
Keywords: Keywords: extracellular vesicles (EVs), urine, lateral flow immunoassay (LFIA), upconverting nanoparticles (UCNPs)